The effects of monoclonal anti‐CD47 on RBCs, compatibility testing, and transfusion requirements in refractory acute myeloid leukemia - Brierley, CK; Staves, J; Roberts, C; Johnson, H; Vyas, P; Goodnough, LT; Murphy, MF (Wiley, 2019)
BACKGROUND CD47 is a novel therapeutic target in the treatment of solid‐organ and hematologic malignancies. CD47 is also expressed on RBCs. Here, we report our experience of the RBC effects and the impact on blood bank testing and transfusion management in a Phase 1 trial of the humanized anti‐CD47 monoclonal antibody Hu5F9‐G4 in relapsed or primary refractory acute myeloid leukemia (AML) (NCT02678338).